Colonial archives: First nation Australians and the First Fleet - MURPHY, EILISH ELLEN CLAIRE (2024)
reserved Exploring the ways in which features of the colonial archive, based on its construction, exclude and include certain voices; particularly those of first nations people in Australia. The period of research is between 1786-1798 as the first fleet of convicts prepare to and invade the continent of Australia for the first time. This exploration delves into characteristics of document acquisition and preservation, revealing the role of public institutions and digital platforms in the collection of knowledge. By analysing the voices within the archive, including governors, settlers, indigenous persons, and individuals in the home country, it sheds light on the power dynamics and narratives of race and racism in the later stages of the period of ‘discovery’. Exploring the ways in which features of the colonial archive, based on its construction, exclude and include certain voices; particularly those of first nations people in Australia. The period of research is between 1786-1798 as the first fleet of convicts prepare to and invade the continent of Australia for the first time. This exploration delves into characteristics of document acquisition and preservation, revealing the role of public institutions and digital platforms in the collection of knowledge. By analysing the voices within the archive, including governors, settlers, indigenous persons, and individuals in the home country, it sheds light on the power dynamics and narratives of race and racism in the later stages of the period of ‘discovery’.